A MOOC to disseminate key concepts related to the future challenges of the French health system. (13th November 2019) - You, C; Lissillour, V; Lefébure, A
Abstract: Background: The increase of life expectancy creates critical health needs that developed countries health systems have to deal with. They are also confronted to persistent health inequalities. A common vision of these issues may not be shared by the health care professionals, decision-makers and citizens. In the context of the launch of new public health laws in France, the French School of Public Health (EHESP) decided to offer a MOOC entitled "Public Health and Health System: transition and transformation" (2019). Objectives: The MOOC intends to raise awareness and increase understanding of public health challenges. It is designed for a wide audience of professionals, decision-makers and citizens in the French speaking world. The content was designed by a multidisciplinary team of academics from the EHESP (N = 50) and a network of health professionals (N = 21). The 6 modules address major themes of the recent health policies, e.g. social and territorial inequalities in health, health care security, health pathways, innovation or health democracy. Results: Over the course of 6 consecutive weeks, almost 7800 people have enrolled in this e-learning. They are provided with short teaching videos (109 capsules of 4-5') and webinars, have access to a number of supplementary reading material and a variety of self-assessment. Active learning is enhanced via forum involving peers and teaching staff. The full course represents around 20 hours of teaching. So far, completion rate has attained 13% which compares well with usual rate for MOOCs. Participants include a wide range of professionals, students and citizens from 87 different countries (72% from France) and 50% had a master or higher degree. The overall satisfaction rate is 98%. Conclusions: This MOOC attracted the attention of a wide and diverse audience regarding the major public health issues. Some public health agencies have expressed interest in implementing the MOOC into their professional development program of their staff. Key messages: Health system reforms are constantly implemented to face new public health challenges. A multidisciplinary MOOC can help raise awareness and understanding of the issue being addressed by new policies.